Proceedings of Seventh International Conference on Bio-Inspired Computing: Theories and Applications (BIC-TA 2012) Volume 2 - Bansal, Jagdish C.; Bansal, Jagdish C.; Singh, Pramod Kumar.; Singh, Pramod Kumar.; Deep, Kusum.; Deep, Kusum.; Pant, Millie.; Pant, Millie.; Nagar, Atulya K.; Nagar, Atulya K. (Advances in Intelligent Systems and Computing, 2013)
The book is a collection of high quality peer reviewed research papers presented in Seventh International Conference on Bio-Inspired Computing (BIC-TA 2012) held at ABV-IIITM Gwalior, India. These research papers provide the latest developments in the broad area of "Computational Intelligence". The book discusses wide variety of industrial, engineering and scientific applications of nature/bio-inspired computing and presents invited papers from the inventors/originators of novel computational techniques.